Preparation of Monodisperse Enrofloxacin Molecularly Imprinted Polymer Microspheres and Their Recognition Characteristics - Xiaoxiao Wang; Yanqiang Zhou; Yuling Niu; Shanwen Zhao; Bolin Gong (International Journal of Analytical Chemistry)
This study presents a new strategy for the detection of enrofloxacin (ENR) in food samples by the use of monodisperse ENR molecularly imprinted polymers (MIPs). Using enrofloxacin as template molecule, methacrylic acid as functional monomer, and ethylene diglycidyl ether as cross-linker, surface molecularly imprinted polymers (MIPs) were prepared on the surface of polymeric glycidyl methacrylate-ethylene glycol dimethacrylate (PGMA-EDMA) microspheres. The surface morphology and imprinting behavior of PGMA-EDMA@MIPs were investigated and optimized. Synthesized PGMA-EDMA@MIPs showed good physical and chemical stability and specific recognition toward fluoroquinolones. The introduction of PGMA-EDMA microspheres greatly increased the adsorption area of PGMA-EDMA@MIPs and increased the adsorption capacity of target molecules. The core shell structure increased the adsorption rate, and adsorption equilibrium was achieved within 6 min, much higher than that of MIPs synthesized by traditional methods. Enrofloxacin in milk samples was detected by molecular imprinting solid phase extraction (MISPE) combined with high performance liquid chromatography (HPLC). Implementing this method resulted in a recovery rate of 94.6~109.6% with a relative standard deviation (RSD) of less than 3.2%. The limit of detection (LOD) of this method was identified as three times the signal-to-noise ratio (10 μg/L). In summary, this work proposed a sensitive, rapid, and convenient method for the determination of trace ENR in food samples.